(untitled) (Texas Journal of Philology, Culture and History, 2023)
Pragmatics and sociolinguistics view the speech acts as the smallest unit of analysis in any speech event. The latter is defined as a “socially accepted” and “patterned sequence” in which the participants of specific speech community are involved. speech community is used to a group of participants who intuitively know how to behave in a speech event. Examples of the speech events are conversations, jokes, sermons, interview, prayers or political speeches (penalosa,198:71)